Effect of methods pretreatment of biomass for yield of biofuels - Bogumił, Dorota (Studia Ecologiae et Bioethicae, 2016)
Due to the growing interest in renewable energy, lignocellulosic biomass is an attractive substrate for the production of biofuels, particularly when it is undeveloped waste. The biomass is cheap, widely available, and has a highenergy value. Conversion technology of this type of biomass is characterized by the limitations associated with a complicated structure of the lignocellulose complex. Various types of pre-treatment of the raw materials is being used to improve its efficiency. The article describes division of available methods for the preparation of lignocellulosic raw materials used to produce various types of biofuels.